On the boundary behavior of solutions of the Beltrami equations - Kovtonyuk, D. A.; Petkov, I. V.; Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We show that every homeomorphic solution of the Beltrami equation $\overline{\partial} f = μ \partial f$ in the Sobolev class $W^{1, 1}_{\text{loc}}$ is a so-called lower $Q$-homeomorphism with $Q(z) = K_{μ}(z)$, where $K_{μ}$ is a dilatation quotient of this equation. On this basis, we develop the theory of the boundary behavior and the removability of singularities of these solutions.